Associations Between Abdominal Obesity Indices and Nonalcoholic Fatty Liver Disease: Chinese Visceral Adiposity Index - Chen, Xueyu; Shi, Fengxue; Xiao, Juan; Huang, Fengyan; Cheng, Fang; Wang, Lihua; Ju, Yanli; Zhou, Yong; Jia, Hongying (Frontiers in Endocrinology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a common chronic liver metabolic disease worldwide. Up to 70-80% of patients with NAFLD were obese, especially abdominal obesity. Many indicators of abdominal obesity have been reported, including waist circumference (WC), visceral obesity index (VAI), lipid accumulation (LAP), and Chinese visceral obesity index (CVAI). However, few studies investigated the associations between these indices with NAFLD. In present study aims to explore the associations between abdominal obesity indices with NAFLD. A total of 7,238 participants were involved in the cross-sectional study, and 1,584 participants were included in the longitudinal study from Jidong communities. NAFLD was assessed by abdominal ultrasonography. The trajectory of WC, VAI, LAP, and CVAI during 2013-2016 was identified by group-based trajectory model. The logistic regression and Cox proportional hazards models analyzed correlations and causality between abdominal obesity indices with NAFLD. In this study, the prevalence and incidence of NAFLD are around 44%, 26%, respectively. In the cross-sectional study, WC, VAI, LAP, and CVAI are both associated with NAFLD. After adjustment for potential confounders, the moderate-rising and high-rising groups of CVAI had the highest risk of NAFLD in longitudinal analysis (HR: 3.978, 95%CI: 2.488-6.363; HR: 5.066, 95%CI: 2.773-9.257, respectively). Receiving operating characteristic curves shows that CVAI with the best diagnosis value for NAFLD (AUC=0.868). CVAI is independently associated with the risk of NAFLD and may also have an important value to the diagnosis of NAFLD.